PERBANDINGAN PENGUNGKAPAN MODAL INTELEKTUAL PERGURUAN TINGGI NEGERI DAN SWASTA DI PULAU JAWA - Tri Wahyudi (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2022)
This research aims to identify disclosure of intellectual capital on the web of public and private universities in Java. This research uses secondary information taken from the college website as the object of study. Intellectual capital items sourced from the framework consist of 46 items, including 8 human capital, 23 structural capital, and 15 relational capital. This research is intended to explain how the disclosure of intellectual capital in public and private universities in Java Island and what distinguishes the disclosure of intellectual capital between public and private universities on the island of Java. The analysis in this research uses a checklist of work paper, after which the calculation of the value of disclosure based on the information is made. Not only by making simple calculations, it is also necessary to try the Mann Whitney test to see if there is a comparison between 2 (two) comparative information. The conclusion from this research is that public and private universities in Java Island mostly disclose intellectual capital in the form of narratives and pictures / graphics. Other results show the asymp value. Sig. (2-tailed) of 0.014 (less than 0.05), which means that there is a significant difference between public and private universities in implementing intellectual capital disclosure.